Pengenalan Konsep Geometri dengan Tangram di TK Masyitoh 04 Sokaraja - Istikaanah, Najmah (Universitas Jenderal Soedirman, 2024)
Every child is born, grows and develops with their own potential and uniqueness. Playing is an important part of a child's learning and development. However, in reality, lately children play games using gadgets more often than studying or playing outside with friends of the same age. Children prefer simple, practical things to entertain themselves and have fun, just sitting comfortably holding their gadgets all day long having fun. This is what makes educational games and activities very important both at school and at home. From this background, the PKM Team carried out the Introduction to Geometry Concepts with Tangram at RA Masyitoh 04 Sokaraja. This activity aims to build geometric thinking from an early age through the Tangram educational game tool in the hope that it can help them when learning geometry at the next level and of course it is expected to reduce dependence on playing games with gadgets. Tangram is an ancient Chinese puzzle that can be used to build geometric reasoning and fine motor skills. The method of implementing PKM activities is: (1) Tangram concept training; (2) Tangram Making Workshop; (3) Tangram Contest. This Community Service activity shows that early childhood children have actually begun to learn about shapes, space, and basic geometric concepts. They use geometric thinking when playing building with blocks, arranging floor puzzles, or playing target games. Thus, children need a variety of educational games so that they can reduce the frequency of playing games using gadgets. Key words: gadget, tangram, geometry